Ziarah Kubur, Marpangir, Mangan Fajar: Tradisi Masyarakat Angkola dan Mandailing Menyambut Bulan Ramadhan dan ‘Idul Fitri - Siregar, Muhammad Andre Syahbana (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the acculturation between Islam and the local culture of the Angkola and Mandailing communities in welcoming the month of Ramadan and the Eid al-Fitr holiday. This research is field research and also library research. The data used are not only sourced from observations and interviews, but also data from books, magazines, newspapers, and others that are supportive and representative. The findings of this study are that Islamic religious rituals and the value of local traditions still go hand in hand in the Islamic communities of Angkola and Mandailing which appear in the tradition of the Ziarah Kubur (Grave Pilgrimage) and Marpangir (Fragrance Bath) on the afternoon before entering the month of Ramadan, and Mangan Fajar (Breakfast at Dawn) at dawn before performing the Eid al-Fitr prayer.Keywords: Religious tradition, local tradition, Ziarah Kubur, Marpangir, Mangan Fajar, Angkola and Mandailing.Â